Моральні емоції та делінквенція: відчуття провини, сорому та співчуття у підлітковій злочинності - Бондзик, Д. М.; Bondzyk, D. M.; Дмитро Бондзик (Габітус. - 2023. - Вип. 49. - С. 170-174, 2023)
Розглянуто поняття моральних емоцій та їхня роль у формуванні поведінки підлітків, зокрема в контексті злочинності. Проаналізовано вплив відчуття провини, сорому та співчуття на злочинну поведінку підлітків, а також їхню роль у підтриманні чи зміні цієї поведінки. Усвідомлення моральних емоцій та їхнього впливу на підліткову злочинність може допомогти розробити стратегії виховання та інтервенцій, спрямованих на зменшення ризику злочинності серед підлітків. Такі стратегії можуть включати розвиток емоційних навичок, стимулювання емпатії та співчуття, а також виховання свідомості про наслідки власних дій.

This article explores moral emotions, including guilt, shame, and compassion, in the context of juvenile delinquency. Juvenile delinquency is a complex problem in modern society, and understanding the moral aspects of this phenomenon is important for the development of effective prevention and rehabilitation strategies. The article examines the concept of moral emotions and their role in the formation of adolescent behavior, in particular in the context of crime. The influence of feelings of guilt, shame and sympathy on the criminal behavior of adolescents is analyzed, as well as their role in maintaining or changing this behavior. Juvenile delinquency is a serious problem in society, and understanding the role of moral emotions can help us develop effective methods of prevention and rehabilitation of young offenders. The main purpose of the article is to consider and analyze these moral emotions in the context of juvenile delinquency. On the basis of available scientific research and data, various aspects of the impact of these emotions on the formation and change of criminal behavior among teenagers will be considered. It is important to note that moral emotions are not the only factors influencing adolescents in the context of crime. Many other factors such as family environment, surrounding social context, education and others can also influence the risk of criminal behavior in adolescents. Understanding moral emotions and their impact on adolescent delinquency can help develop educational strategies and interventions aimed at reducing the risk of adolescent delinquency. Such strategies may include developing emotional skills, fostering empathy and compassion, and fostering awareness of the consequences of one's actions. Overall, understanding moral emotions and their impact on adolescents will help develop effective approaches to crime prevention and promote their positive development.

Рассмотрены понятия нравственных эмоций и их роль в формировании поведения подростков, в частности в контексте преступности. Проанализировано влияние чувства вины, стыда и сочувствия на преступное поведение подростков, а также их роль в поддержании или изменении этого поведения. Осознание нравственных эмоций и их влияние на подростковую преступность может помочь разработать стратегии воспитания и интервенции, направленные на уменьшение риска преступности среди подростков. Такие стратегии могут включать развитие эмоциональных навыков, стимулирование эмпатии и сострадания, а также воспитание сознания о последствиях собственных действий.
Moral emotions a nd delinquency: guilt, shame and empathy in adolescent offending
Keywords: моральні емоції; moral emotions; моральные эмоции; підліткова злочинність; teenage criminality; подростковая преступность; відчуття провини; feeling guilty; чувство вины; сором; shame; стыд; співчуття; compassion; соболезнования; профілактика; prevention; профилактика; реабілітація; rehabilitation; реабилитация; підлітки; teenagers; подростки